PERANCANGAN VIDEO GAME DENGAN METODE GAME DEVELOPMENT LIFE CYCLE MENGGUNAKAN UNITY - Ahmadien Hafizh Yusufi (2024)
The COVID-19 pandemic has significantly impacted social facilities, leading to increased demand for video games. The gaming industry in Indonesia has experienced significant growth, with the gaming market reaching Rp. 650,86 billion, or $416,90 million USD. The growth of video games has led to a need for game developers to create innovative and innovative experiences. One effective approach is the Game Development Life Cycle (GDLC), which provides systematic and structured work for game development. Unity, a popular game development platform, also plays a crucial role in creating a successful game. The integration of GDLC and Unity allows for the creation of a high-quality and engaging game experience. Integration of Unity and GDLC can lead to better game quality and stability.